Eficácia do paration metílico e do extrato aquoso de folhas secas de nim no controle de anacanthorus penilabiatus (monogenoidea) em pacu (piaractus mesopotamicus) - da Cruz, Claudinei [UNESP]; Machado Neto, Joaquim Goncalves [UNESP]; Fujimoto, Rodrigo Yudi; Peixoto Henares, Matheus Nicolino [UNESP]; Duo, Daniela Avilez [UNESP] (Inst Pesca, 2008)
This work determined the efficacy of the insecticide methyl parathion and the natural pesticide azadirachtin present in the aqueous extract of dry neem leaves (AEDNL) to Anacanthorus penilabiatus (Monogenoidea) control in pacu (Piaractus mesopotamicus). The efficacy of methyl parathion was evaluated in an experiment consisting of six treatments (0.0, 3.0, 4.0, 5.0, 6.0 and 7.0 mg methyl parathion/L water) and five exposure times (2, 4, 8, 16 and 24 h). The efficacy of azadirachtin present in AEDNL was assessed in an experiment consisting of seven treatments (0,0; 25; 50; 75; 100; 125; e 150 mL/L water) and five exposure times (24, 48, 72, 96 and 120 h). The efficacy of methyl parathion increased with increasing concentration and exposure time. The highest control efficacy was obtained with a concentration of 7 mg methyl parathion/L at all exposure times. In this treatment, the highest efficacies were observed at 16 and 24 h of exposure, with a control rate of 96.2 and 97.0%, respectively. For the AEDNL, the highest control efficacy (89.2%) was obtained with a concentration of 2.9 mg/L after 120 h of exposure. The efficacy in the treatments employing 1.47 and 1.18 mg/L was 83.9 and 82.5%, respectively, after 120 h of exposure. Methyl parathion presented a higher efficacy in the control of A. penilabiatus than the AEDNL. The AEDNL was moderately effective in the control of the parasite.
Efficacy of the methyl parathion and the aqueous extract of dry neem leaves in the control of anacanthorus penilabiatus (monogenoidea) in pacu (piaractus mesopotamicus)
Keywords: Piaractus mesopotamicus; treatment; efficacy; parasites; methyl parathion; neem